2001
DOI: 10.3168/jds.s0022-0302(01)74524-9
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference for Categorical Traits with an Application to Variance Component Estimation

Abstract: We implemented statistical models of Bayesian inference that included direct and maternal genetic effects for genetic parameter estimation of categorical traits by Gibbs sampling. The estimation errors and variances of estimates of animal versus sire and maternal grandsire models, of linear versus threshold models, of single-trait versus multiple-trait models, and of treating herd-year-season as fixed versus random effects in the model were compared. The results indicated that linear models yielded biased esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
3
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 21 publications
3
71
3
3
Order By: Relevance
“…Application of threshold animal models to categorical traits was often problematic because of the 'extreme category problems' where all observations for some subclasses are in the same category (Misztal et al, 1989). Luo et al (2001) showed also that threshold animal models had problems with convergence, and yielded biased estimates when convergence was reached. The threshold model gave biased variances for herd-year and additive genetic effects.…”
Section: Methodsmentioning
confidence: 99%
“…Application of threshold animal models to categorical traits was often problematic because of the 'extreme category problems' where all observations for some subclasses are in the same category (Misztal et al, 1989). Luo et al (2001) showed also that threshold animal models had problems with convergence, and yielded biased estimates when convergence was reached. The threshold model gave biased variances for herd-year and additive genetic effects.…”
Section: Methodsmentioning
confidence: 99%
“…Effects of data structure on accuracy of genetic parameter estimates have been discussed elsewhere (Stock et al, 2007). In addition to the four binary traits of interest, one continuous trait was included in order to improve mixing and convergence of the Gibbs sampler (Luo et al, 2001) and accuracy of genetic evaluation (Janss and Foulley, 1993;Varona et al, 1999). However, inclusion of a correlated continuous trait does not warrant unbiased estimates of genetic parameters in a complex multiple-trait setting as used for this simulation (Stock et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that used animal models for analyses with categorical data (Luo, Boettcher, & Schaeffer, 2001;Phocas & Laloe, 2003) reported difficulty to achieve Gibbs chain convergence chain , which was not observable in this study as verified in Figures 2, 3 and 4.…”
Section: Resultsmentioning
confidence: 47%